2003
DOI: 10.1046/j.1528-1157.2003.15101.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Asystole in Epilepsy: Clinical and Neurophysiologic Features

Abstract: Summary:  Purpose: Cardiac asystole provoked by epileptic seizures is a rare but important complication in epilepsy and is supposed to be relevant to the pathogenesis of sudden unexplained death in epilepsy (SUDEP). We sought to determine the frequency of this complication in a population of patients with medically intractable epilepsy and to analyze the correlation between EEG, electrocardiogram (ECG), and clinical features obtained from long‐term video‐EEG monitoring.Methods: Retrospective analysis of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
189
1
24

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 238 publications
(227 citation statements)
references
References 28 publications
(28 reference statements)
10
189
1
24
Order By: Relevance
“…One might predict that pallor would be more common in ictal syncope than in other seizures, but this could not be determined in our study. It has been suggested that prolonged post-ictal confusion might be a clue to the diagnosis of ictal bradycardia [17]. However, the post-ictal recovery period in ictal asystole and non-asystolic seizures was not significantly different in our series.…”
Section: Discussioncontrasting
confidence: 77%
“…One might predict that pallor would be more common in ictal syncope than in other seizures, but this could not be determined in our study. It has been suggested that prolonged post-ictal confusion might be a clue to the diagnosis of ictal bradycardia [17]. However, the post-ictal recovery period in ictal asystole and non-asystolic seizures was not significantly different in our series.…”
Section: Discussioncontrasting
confidence: 77%
“…5 6 The mean prevalence of ictal asystole in all people with refractory focal epilepsy admitted for a vEEG recording was 0.318% (95% CI 0.316% to 0.320%). [7][8][9][10][11] Ictal asystole was only reported in people with focal epilepsy (table 1). Most of the ictal asystoles occurred during the course of a focal dyscognitive seizure (formally known as a complex partial seizure), on average starting 30 s after seizure onset.…”
Section: Ictal Asystolementioning
confidence: 99%
“…6 Ictal bradyarrhythmias have been postulated to be secondary to vagal cardiac activation. 7 However, it is not clear whether bradyarrhythmias are from vagal-mediated activation of cardiac function or uncoordinated autonomic effect. 7,8 Prior case reports have demonstrated that ictal bradyarrhythmias begin between 5 and 20 seconds after ictal discharge in partial seizures and 60 and 100 seconds in generalized seizures.…”
Section: Discussionmentioning
confidence: 99%